Preparing Future Journalists for Trauma on the Job. (March 2020) - Hill, Desiree; Luther, Catherine A.; Slocum, Phyllis
Journalists are not immune from the emotional impact of their work as they report on mass shootings, terror attacks, and natural disasters. Adding to an established body of research on the interrelationship between journalism and trauma, this syndicate focused on how journalism schools should prepare students to deal with traumatic news content and events that would undoubtedly form part of their future day-to-day activities.